Dual-peptide ligand masks: a proposed treatment approach to stop prion disease dementias. Issue 1 (January 2020) - Roe, Kevin
Highlights: Prion disease dementias are currently not practically treatable. A treatment approach using dual-peptide ligand masks to stop prion diseases offers many advantages. One treatment uses modified bacteria in gastrointestinal tracts to make dual-peptide ligand masks. Another treatment does not introduce genetically modified bacteria. Abstract : Prion disease dementias are currently not practically treatable. However, a proposed treatment approach using specifically targeted dual-peptide ligand masks can mask prion surface proteins and treat specific prion diseases. Different approaches might be used to treat these prion diseases. One treatment introduces genetically modified cells into the gastrointestinal tract or other locations to produce dual-peptide ligand masks; and another treatment introduces only the dual-peptide ligand masks into the center of prion infections to mask prion surface proteins. An independent group introduced genetically modified therapeutic bacteria into large numbers of mammals, including several human volunteers, with safe and effective experimental results, without long-term colonization by the bacteria, which experimentally supports the feasibility of the first treatment. These approaches offer several advantages compared with other potential treatments against prion diseases in humans.